Economic analysis of rice and common bean production in succession to green manure crops and mecahnical soil decompression in Brazilian Savannah 1 - Nascimento, Vagner Do [UNESP]; Arf, Orivaldo [UNESP]; Tarsitano, Maria Aparecida Anselmo [UNESP]; Garcia, Nayara Fernanda Siviero [UNESP]; Penteado, Mariele De Souza [UNESP]; Sabundjian, Michelle Traete [UNESP] (Universidade Federal de Viçosa, 2016)
The previous cultivation of green manures and mechanical soil decompression are options to minimize compaction of the topsoil in no-tilage system (NTS) set in different production systems in the Brazilian Savannah. In addition, it is essential to relate these agricultural practices with the economic benefits generated through the production cycles. The objective of this study was to evaluate economically the effect of sporadic mechanical decompression of the soil and previous cultivation of green manure in the production and net gain margin of upland rice and winter common bean, under sprinkler irrigation, in NTS in lowland Brazilian savannah. This study was developed in the 2012/13 harvest and 2013 winter in Selvíria, state of Mato Grosso do Sul, in an clay texture Oxisol in the savanah in the state of Mato Grosso do Sul, in a randomized block design arranged in a 5 x 2 factorial arrangement with four replications. The treatments were a combination of five green manures (fallow (control), Cajanus cajan, Crotalaria juncea, Pennisetum glaucum and Urochloa ruziziensis) with and without mechanical soil scarification. The yields of upland rice and common bean grains were not influenced by the previous green manure cultivation; the upland rice grown in succession to Cajanus cajan in the presence of mechanical soil scarification provided greater increase in grain yield and higher gross margin profit. Beans cultivated in succession to Crotalaria juncea and Pennisetum glaucum in the presence of mechanical soil scarification, followed by rice cultivation, provided greater increases in grain yield and gross profit margins.

O cultivo antecessor de adubos verdes e a descompactação mecânica do solo são opções para minimizar a compactação da camada superficial do solo em sistema plantio direto (SPD) implantado, em diversos sistemas de produção no cerrado. Além disso, é essencial relacionar estas praticas agrícolas com os benefícios econômicos gerados. Assim, este trabalho objetivou avaliar economicamente o efeito da descompactação mecânica esporádica do solo e cultivo antecessor de adubos verdes, na produtividade e margem liquida do ganho para o arroz de terras altas e feijão de inverno, sob irrigação por aspersão, em SPD em área de cerrado de baixa altitude. Este estudo foi desenvolvido na safra 2012/13 e no inverno de 2013 em Selvíria, MS, em um Latossolo Vermelho distrófico de cerrado Sul Mato Grossense de textura argilosa, com delineamento em blocos casualizados disposto em esquema fatorial 5x2, com quatro repetições. Os tratamentos foram constituídos pela combinação de cinco adubos verdes (pousio (controle), Cajanus cajan, Crotalaria juncea, Urochloa ruziziensis e Pennisetum glaucum) com e sem escarificação mecânica do solo. As produtividades de grãos do arroz e feijão não foram influenciadas pelo cultivo antecessor de adubos verdes; o arroz de terras altas cultivado em sucessão a Cajanus cajan, na presença de escarificação mecânica do solo, proporcionou maior acréscimo de produtividade de grãos e maior margem de ganho bruta. O feijão cultivado em sucessão a Crotalaria juncea e Pennisetum glaucum, na presença de escarificação mecânica do solo, seguida de cultivo do arroz, proporcionaram maiores acréscimos na produtividade de grãos e nas margens de ganho brutas.
Análise econômica da produção de arroz e feijão em sucessão a cultivos de adubos verdes e descompactação mecânica no cerrado
Keywords: Phaseolus vulgaris L; Oryza sativa L; profit margin; cover crops; sprinkler irrigation; no-tilage system; Phaseolus vulgaris L; Oryza sativa L; margem de ganho; plantas de cobertura; irrigação por aspersão; sistema plantio direto